Sustainability assessment of a novel micro solar thermal: Biomass heat and power plant in Morocco. (16th June 2020) - Herrera, Israel; Rodríguez‐Serrano, Irene; Garrain, Daniel; Lechón, Yolanda; Oliveira, Armando
Abstract: Novel renewable energy technologies in the Middle East and North Africa region can be developed through microgeneration systems aiming to supply local energy demands in a sustainable way. In this study, we carried out a sustainability assessment combining two reputable methodologies which have been applied to a facility comprising a hybrid solar/biomass micro‐cogeneration organic ranking cycle system located in Morocco. We first applied a multiregional input–output analysis where economic issues such as the production of goods and services generated in all project's phases, as well as the added value and employment created, are estimated. Then, environmental impacts were assessed through a life cycle assessment (LCA). In terms of socioeconomic analysis, the total production of goods and services shows a value of 1.18 €2015 /kWh. The added value and employment creation were 0.56 €2015 /kWh and 0.05 full‐time employees/MWh, respectively. The levelized cost of electricity results in 0.218 €2015 /kWh and the multiplier effect amounts to 2.26. The largest increase in sectorial output is produced in the Moroccan electricity sector and the largest job creation takes place in the agriculture sector from the biomass supply. Regarding environmental results, LCA shows a climate change potential of 11.8 g CO2 eq/kWhel, of which more than 70% comes from the boiler operation and specifically from the emissions due to biomass transportation. These results can help in promoting micro solar‐biomass systems in Morocco as they identify the socioeconomic and environmental benefits that can counterbalance the higher costs of such systems compared to fossil technologies.